A medical expert system for the diagnosis of hypertensive disorders in pregnancy / Azizah Sulaiman - Azizah, Sulaiman (1989)
This thesis describes and discusses the implementation o f a medical expert system for the diagnosis of hyper~ension in pregnancy. The system named HiP, consists of a consultation program and a knowledge base editor. The consultation program of HiP is an interactive program that attempts at assisting nurses in absence of a specialist, in the diagnosis of hypertension and its associated disorders in pregnant women. The system uses the much publicised rule-based approach of MYCIN, largely because of its favourable performance. Hip employs a depth-first search with a backward chaining of rules as its control strategy. The system always starts its inference with a goal to establish and the system works on establishing this goal by examining the rules, condition by condition. HiP's performance is evaluated by running the system through a set of real cases of hypertensive nd pregnant patients over the past year at the University Hospital, Kuala Lumpur. The diagnoses made by HiP are compared against that made by the doctors in charge and the result of the comparison is shown to an expert or comment. Written in GCLISP and developed on an IBM or IBM compatible personal or micro-computers, Hip is targeted use at the rural clinics where computer facilities are usually source.